I-V model for short gate length ion-implanted GaAs OPFETs - Tripathi S.; Jit S. (My University, 2025)
The current-voltage characteristics for optically controlled short gate-length ion-implanted GaAs MESFET has been presented in this paper. The illumination sensitivity of the drain-source current has been analyzed. It is shown that good agreements are obtained between the developed model and the numerical simulation data obtained by ATLAS™ two-dimensional (2D) device simulator. © 2011 IEEE.